Stressprävention durch Motto-Ziele: Eine Kurzanalyse der Zielbildung und individuellen Selbstkongruenz von Lernenden in Coaching und Lehre - Karin Meyer (IU Internationale Hochschule, 2022)
– The current working world 4.0 is often referred to as VUCA. This is associated with trends such as increasing flexibility, acceleration, digitization and information overload, which push companies and employees to their limits. This also leads more and more people to pursue externally determined goals that do not correspond to them and their inner guidance. One goal is therefore to find jobs and positions that really suit the person. This contrasts with the dropout rates of students in bachelor's degree programs at universities, which are around 30% across all degree programs. A similar picture emerges in the area of dual training: Here, too, around 30% of apprenticeships are terminated prematurely. Students in graduating classes report that they have difficulty finding the career path that fits them as a person. They report the feeling of stress and anxiety. There is also a fear of making the wrong decision in a phase that forms the basis for further career and life, and which for the first time allows the greatest possible freedom far away from predetermined school curricula. Observations in teaching and coaching show that not only students but also adults are characterized by a lack of superordinate and self-congruent goals, which in retrospect cause stress, dissatisfaction and inner conflicts. In this situation, motto goals can make a positive contribution to stress reduction or prevention and can pave the way for the future.
Keywords: 650; Stress management; stress reduction; VUCA; goals; goal setting of students and coachees